(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The importance of nutrition in sports performance has been recognized since the dawn of civilization. Along with Sumerians, Egyptians, the Chinese, and other ancient cultures, the Indian people were among the first to pursue a nutritious diet and a meaningful lifestyle in the face of environmental obstacles. Sports nutrition is a specialization within the field of nutrition that partners closely with the study of the human body and exercise science. Sports nutrition can be defined as the application of nutrition knowledge to a practical daily eating plan focused on providing the fuel for physical actively. Facilitating the repair and rebuilding process following hard physical work, and optimizing athletic performance in competitive events, while also promoting overall health wellness. and the study which discussed about Importance of Proper Nutrition in Sportsmen, Prerequisites of High Level Sports Performance, Sports Performance, Profile of functional indicators of nutritional status, Heart rate, Effect of liquid supplementation on performance indicators.